2014
DOI: 10.1016/j.physa.2014.03.045
|View full text |Cite
|
Sign up to set email alerts
|

A Bohr-type model of a composite particle using gravity as the attractive force

Abstract: We formulate a Bohr-type rotating particle model for three light particles of rest mass mo each, forming a bound rotational state under the influence of their gravitational attraction, in the same way that electrostatic attraction leads to the formation of a bound proton-electron state in the classical Bohr model of the H atom. By using special relativity, the equivalence principle and the de Broglie wavelength equation, we find that when each of the three rotating particles has the same rest mass as the rest … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 28 publications
3
64
0
Order By: Relevance
“…It is found that such rotational states exist and their properties are similar with those computed by treating the two-or three-rotating particle motion via the combination of HUP, special relativity, Newton's gravitational law and the equivalence principle [5,6,7]. Interestingly when the rest mass of the two or three light relativistic particles is in the range of neutrino masses (∼ 5 · 10 −2 eV /c 2 ), then the mass of the gravitationally confined microscopic Planckian or sub-Planckian rotating particle states are in the hadron ( 1 GeV ) mass range [5,6,7].…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…It is found that such rotational states exist and their properties are similar with those computed by treating the two-or three-rotating particle motion via the combination of HUP, special relativity, Newton's gravitational law and the equivalence principle [5,6,7]. Interestingly when the rest mass of the two or three light relativistic particles is in the range of neutrino masses (∼ 5 · 10 −2 eV /c 2 ), then the mass of the gravitationally confined microscopic Planckian or sub-Planckian rotating particle states are in the hadron ( 1 GeV ) mass range [5,6,7].…”
Section: Introductionsupporting
confidence: 53%
“…The corresponding relativistic mass γm o equals 313 M eV /c 2 which falls in the range of effective quark masses [13]. Consequently, as already shown [5,6,7], the mass of quarks can be modeled successfully by the mass of gravitationally confined neutrinos.…”
Section: Sr Treatmentmentioning
confidence: 64%
See 3 more Smart Citations